A new species of planthopper in genus Herpis (Hemiptera: Derbidae) from lowland tropical rainforest in Costa Rica - Bahder, Brian W.; Echavarria, Marco A. Zumbado; Barrantes, Edwin A. Barrantes; Helmick, Ericka E.; Bartlett, Charles R. (Zootaxa, 2021)
Recent survey efforts in the Neotropics have documented a variety of new species of planthoppers associated with palms. Herein, a new species, Herpis soros sp. n., is described from palms in lowland tropical rainforest from Costa Rica. Other species in the genus (H. metcalfi, H. albida, and H. fuscovittata) are evaluated to provide an updated diagnosis of the genus Herpis. The New World Phaciocephalus is examined because two species were described in the genus Herpis with P. fimbriolata being recorded for both Herpis and Phaciocephalus. After examining holotype material for the New World Phaciocephalus, two species were determined to belong to other genera resulting in new combinations Oropuna orba comb. n. and Persis (Anapersis) pallidovenosa comb. n. The synonymy of Syntames with Herpis is reviewed, with S. fuscus moved to Oropuna as Oropuna fusca comb. n. Finally, molecular analysis of the new species based on COI and 18S show strong support for H. soros sp. n. as a distinct clade relative to all other cenchreines available.